Physical Modeling of Flow in a Tundish for Continuous Casting Machine - Maria Carnogurska; Miroslav Prihoda (Communications - Scientific letters of the University of Zilina, 2012)
The paper describes a procedure for obtaining similarity criteria for a real object – a tundish for continuous casting machine (CCM) and its reduced physical model. The procedure is demonstrated on the basis of Navier-Stockes differential equations and with the help of dimensional analysis. To obtain similarity criteria dimensional analysis makes use of dimensions of those physical quantities which significantly influence the mentioned phenomenon. From the above it results that when modeling a concrete phenomenon with the help of this method it is inevitable to thoroughly know the physical substance of the phenomenon to expressly ensure the choice of all relevant quantities. On the basis of elaborated model laws the basic characteristics of flow (rate, flow volume, time intervals) were designed for the reduced model of the real CCM. The obtained dependences of characteristics feature the universal validity for all the models of tundishes.